Kadar Kurkumin Dari Ekstrak Beberapa Rimpang Suku Zingiberaceae - Riza R Yustinianus; Jeanny Wunas; Yusnita Rifai; Naimah Ramli (STIFA Makassar, 2019)
Research about curcumin content in extract of some rhizomes from zingiberaceae Family had been done. This research aimed to determine the content of curcumin in turmeric rhizome extract (Curcuma domestica Val.), Curcuma xanthorriza Roxb, Curcuma mangga Val., Curcuma zedoaria (Berg) Rosc. and Curcuma aeruginosa Roxb. using thin layer chromatography densitometry (TLC-densitometry) method based on the area of the rhizomes extract and curcumin standard. Each sample was extracted by soxhlet with acetone as solvent. Content of curcumin in the extracts was obtained using TLC with the silica gel GF254 as stationary phase and chloroform: methanol (95 : 5) as mobile phase and was analyzed using TLC-densitometer and measured at 420 nm. Results showed that curcumin content from each extract was found in C. domestica, C. xanthorrhiza, C. aeruginosa, C. mangga, C. zedoaria were 11.33, 5.95, 2.80, 1.80 and 0.60%.